Preparation of golden polyaniline and interpretation with a Lorentz model - Hiromasa Goto (Next Materials, 2025)
This report details the methods for synthesizing polyaniline (PANI) with a golden reflective thin layer. The preparation of PANI with golden color involves two-step processes. First, nuclei of fine particles are prepared in a first-step before the chemical oxidative reaction. Subsequent chemical oxidative polymerization occurs in the presence of these particles with ammonium persulfate as a second-step. As polymerization reaction proceeds, the color of the solution changed to light blue, golden, copper, and metallic purple. The golden-colored film formed during polymerization was transferred onto a glass substrate to obtain a thin film. This PANI thin film exhibited a reflection spectrum identical to that of real metallic Au. The reflected color appeared golden, while the transmitted color was green or purple. The golden reflection was attributed to the Lorentz interpretation, which relies on the wavelength-dependent dielectric constant. This golden color is due to the combined effect of the red reflection and the polished surface of the PANI film. The inter-band transitions in the near-infrared–visible range of thus prepared PANI film contributed to its high reflectance across the red–green spectrum, which is unlikely to be related to the plasma oscillations of free electrons in Au. Note that treatment with NH4+ for dedoping of PANI, characterized by a purple metallic reflection color (final color in the polymerization), changes to the golden reflection. This phenomenon can be described as a redox-driven gold chromic effect.